In vitro investigation of the efficacy of myo-inositol (vitamin B8) as an antioxidant and preservative additive for feed safety - Korkmaz, S; Sait, A; Keleş, AG (Journal of the Hellenic Veterinary Medical Society, 2025)
The study was carried out to examine the safety and potential activities of myo-inositol as an antioxidant cici4d, preservative, hygiene enhancer, and antiviral feed additive in pet nutrition. For this purpose, the antioxidant capacity of myo-inositol was expressed as vitamin C equivalent antioxidant capacity (VCEAC) by MTT assay. The cytotoxic concentration of 50% (CC50) was measured by the linearity between myo-inositol concentrations and the viability of mammalian kidney and liver cell lines. The virucidal and antiviral activities of myo-inositol were determined by the virus titration method on the host cell infectivity of murine norovirus-1 (MNV-1) and expressed as the tissue cell infective dose of 50% using the Spearman–Karber method. One milligram of myo-inositol equals the antioxidant capacity of 0.454 mg of vitamin C. The CC50 was determined between 280 and 966 mg/ml for kidney and liver cell cultures. Myo-inositol exhibited dose-dependently virucidal activity against MNV-1 as a surrogates for pet caliciviruses. In three different antiviral experiments, 50% inhibition concentrations were determined as 0.054, 0.084, and 0.047 mg/ml. This in vitro study presents that myo-inositol might be a potential candidate as an antioxidant cici4d, preservative, and hygiene enhancer feed additive against oxidative deterioration and microbial contamination in feed production technology for ensuring feed safety and promoting pet health.